Among the dead cities the history and moral legacy of the WWII bombing of civilians in Germany and Japan - Grayling, A.C (Walker & Company, 2006)
"Was the bombing offensive [against civilians in Germany and Japan] a crime against humanity," writes A. C. Grayling, "or was it justified by the necessities of war? These questions mark one of the great remaining controversies of the Second World War." Their resolution, which Grayling accomplishes with great respect and with a sense of urgency, is a vital contribution to the debate about how far governments can go in the name of national security.